The physician in the face of death in the emergency room - Janaína de Souza Aredes; Karla Cristina Giacomin; Josélia Oliveira Araújo Firmo (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE: To analyze how physicians, as part of a sociocultural group, handle the different types of death, in a metropolitan emergency service. METHODS: This is an ethnography carried out in one of the largest emergency services in Latin America. We have collected the data for nine months with participant observation and interviews with 43 physicians of different specialties - 25 men and 18 women, aged between 28 and 69 years. RESULTS: The analysis, guided by the model of Signs, Meanings, and Actions, shows a vast mosaic of situations and issues that permeate the medical care in an emergency unit. The results indicate that physicians may consider one death more difficult than another, depending on the criteria: age, identification or not with the patient, circumstances of the death, and medical questioning as to their responsibility in the death process. CONCLUSIONS: For physicians, no death is easy. Each death can be more or less difficult, depending on different criteria that permeate the medical care in an emergency unit, and it reveals different social, ethical, and moral issues.